Benchmarking total hip replacement constructs using noninferiority analysis: the New Zealand joint registry study - Michael Wyatt; Chris Frampton; Michael Whitehouse; Kevin Deere; Adrian Sayers; David Kieser (BMC Musculoskeletal Disorders, 2021)
Abstract Background The aim of this study was to compare the relative performance of total hip replacement constructs and discern if there is substantial variability in performance in currently commonly used prostheses in the New Zealand Joint Registry (NZJR) using a noninferiority analysis. Methods All patients who underwent a primary total hip replacement (THR) registered in the NZJR between 1st January 1999 to June 2020 were identified. Using a noninferiority analysis, the performance of hip prostheses were compared with the best performing contemporary construct. Construct failure was estimated using the 1-Kaplan Meier survival function method to estimate net failure. The difference in failure between the contemporary benchmark and other constructs was examined. Results In total 135,432 THR were recorded comprising 1035 different THR constructs. Notably 328 constructs were used just once. Forty-eight constructs (62,251 THR) had > 500 procedures at risk at 3 years post-primary of which 28 were inferior by at least 20% relative risk of which, 10 were inferior by at least 100% relative risk. Sixteen constructs were identified with > 500 procedures at risk at 10 years with 9 inferior by at least 20%, of which one was inferior by > 100% relative risk. There were fewer constructs noninferior to the best practice benchmark when we performed analysis by gender. In females at 10 years, from 5 constructs with > 500 constructs at risk, 2 were inferior at the 20% margin. In males at 10 years, there were only 2 eligible constructs of which one was inferior at the 20% margin. Conclusions We discerned that there is substantial variability in construct performance and at most time points, just over half of constructs are inferior to the best performing construct by at least 20%. These results can facilitate informed decision-making when considering THR surgery.